Less Commonly Taught Language Instructors: An Updated Look at Instructor Profiles and Needs - Emily Heidrich Uebel; Bethany Zulick (Journal of the National Council of Less Commonly Taught Languages)
It has been over 20 years since Johnston and Janus (2003) conducted their survey of LCTL instructor professional development needs in higher education; there was a need to conduct another survey to understand the current landscape, taking into account the many changes in the field. The current study begins to fill this gap with an updated survey (conducted in 2021) that focuses on instructor profiles and pressing development needs in general as well as topics specifically related to communities of practice, instructional materials, and technology. Compared to the earlier study, results show that LCTL instructors (n=80) are now on more tenuous contracts, but may have more training in pedagogy than previous studies indicate. In addition, desire for training in technology has become less of a focus, while the need for connection and community remains high. Suggestions for new and continued areas of focus are discussed